Kristus sebagai Jembatan: Peran Kristus dalam Memediasi Perjumpaan dengan Allah - Yuwita Despriyantie; Natalia Natalia; Yohana Katerina Tinopi; Sarmauli Sarmauli (LPPM - STT Kadesi Bogor, 2024)
Christ as the mediator between humans and God in Christian teachings, based on the Bible and Christian theology. The aim is to deepen understanding of Christ's role as mediator and its implications in the spiritual life of Christians. Biblical analysis methods are used to support the finding that Christ is the only way to God. The implications include strengthening spiritual connections, influencing the way Christians worship and pray, and deepening understanding of God's infinite love. This conclusion leads to an understanding that Christ as an intermediary strengthens faith and steadfastness in living daily life, as well as bringing comfort and hope to His people in facing life's challenges. This provides a foundation for further research in understanding the concept of Christ as mediator and its implications in religious practice and interreligious dialogue.